2012
DOI: 10.13181/mji.v21i1.471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of primaquine and ritonavir interaction on CYP3A4 mRNA expression in HepG2 cell culture

Abstract: Abstrak AbstractBackground: Concomitant treatment with antimalaria and antiretroviral drug is a new challenge in the management of malaria and HIV co-infection. Primaquine is a substrate and also an inhibitor of CYP3A4, while ritonavir is a substrate, an inhibitor, and also an inducer for CYP3A4. the objective of this study is to measure the CYP3A4 mRNA expression in HepG2 cell culture induced by primaquine and ritonavir co-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…In vitro, HepG2 cells can produce CYP3A4 enzymes known to metabolize more than 50% of drugs. 59,60 Madin-Darby canine kidney (MDCK) cells are known to be widely used for drug elimination, permeability, and drug solubility tests in vitro, so it is hoped that MO extracts will have a low toxicity effect. 61,62 Our study showed that the toxicity dose of ethanol extract MO was 6-7 times higher than the antioxidant dose in HepG2 cells and 8 times in MDCK cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, HepG2 cells can produce CYP3A4 enzymes known to metabolize more than 50% of drugs. 59,60 Madin-Darby canine kidney (MDCK) cells are known to be widely used for drug elimination, permeability, and drug solubility tests in vitro, so it is hoped that MO extracts will have a low toxicity effect. 61,62 Our study showed that the toxicity dose of ethanol extract MO was 6-7 times higher than the antioxidant dose in HepG2 cells and 8 times in MDCK cells.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was synthesized by reverse transcription of each RNA sample using ReverTra Ace® qPCR RT Master Mix (Toyobo Co., Ltd, Tokyo, Japan), according to the manufacturer's instructions. The quantitative evaluation of mRNA expression was carried out by real‐time PCR with the cDNA samples using SsoFast EvaGreen Supermix (Bio‐Rad Laboratories, Inc., CA) with the gene specific primers as follows: forward and reverse primers, Mdr1a were 5′‐TGA ACT GTG ACC ATG CGA GAT GTT AAA TA‐3′ and 5′‐GTC TCT GAA GAC TCT AAA ATG GAC TAA ATG‐3′ (153 bp ) (Higashi et al, ); Bcrp, 5′‐CAA TGG GAT CAT GAA ACC TG‐3′ and 5′‐GAG GCT GGT GAA TGG AGA A‐3′ (536 bp ) (Shibayama et al, ); Pept1 , 5′‐CAC AGC GCC AGC AAC TAT CA‐3′ and 5′‐GAT ATT ACC GAT GGC CAC GG‐3′ (360 bp ) (Naruhashi, Sai, Tamai, Suzuki, & Tsuji, ); β‐actin , 5′‐TCA GCA AGC AGG AGT ATG‐3′ and 5′‐GTC AAG AAA GGG TGT AAC G‐3′ (97 bp ) (Iskandarmudasyah, Louisa, Arleni, Jusman, & Suyatna, ). Real‐time PCR was performed using a thermal cycler CFX96TM Real‐TimeSystem (Bio‐Rad Laboratories, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Suspen sel yang telah cair dimasukkan ke dalam medium DMEM yang sebelumnya telah disiapkan. Kultur sel dilakukan pada suhu 37°C dengan CO2 5% [11].…”
Section: Kultur Sel Hepg2unclassified
“…Kultur sel dipindahkan ke dalam tabung kriopreservasi 1,8 mL dan dimasukan ke dalam freezer -80°C selama satu malam. Kemudian kultur sel tersebut dipindahkan ke dalam cryotank berisi nitrogen cair (-196°C) [11].…”
Section: Kultur Sel Hepg2unclassified